(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate left ventricular global longitudinal strain in patients with systemic lupus erythematosus, and to identify factors associated with impaired global longitudinal strain in this population. Methods: A cross-sectional study was conducted on 69 systemic lupus erythematosus patients diagnosed according to the SLICC (2012) or EULAR (2019) criteria. All patients underwent two-dimensional speckle tracking echocardiography using GE Vivid S70 (with AFI software). Global longitudinal strain was measured from three apical views: 2-chamber, 3-chamber, and 4-chamber. Clinical data, laboratory parameters, SLEDAI scores, and disease activity levels were collected and analyzed. Results: The mean global longitudinal strain was -18.5 ± 3.3%. When classified using a threshold of -18%, 40.6% of patients (28/69 = 40.6%) had reduced global longitudinal strain, reflecting a high prevalence of subclinical myocardial dysfunction. Reduced global longitudinal strain was more common in patients with renal impairment, proteinuria, elevated SLEDAI score, low EF, and decreased septal e’ velocity. Conclusion: Global longitudinal strain is a valuable and sensitive tool for early detection of subclinical left ventricular dysfunction in systemic lupus erythematosus. Routine global longitudinal strain monitoring is recommended for high-risk patients, such as those with high disease activity, nephrotic syndrome, hypertension, or elevated BMI and heart rate.